Psychosocial Factors Affecting Smoking Cessation Among People Living With Schizophrenia: A Lived Experience Lens - Cocks, Nadine; Brophy, Lisa; Segan, Catherine; Stratford, Anthony; Jones, Simon; Castle, David (Frontiers in Psychiatry, 2019)
Introduction: People living with schizophrenia smoke at much higher rates than the general population, and find it more difficult to quit. To date, lived experience has received little attention from researchers. Personal recovery perspectives may generate further insights into established psychosocial barriers and enablers of smoking cessation. Methods and Results: A lived experience account is provided by one of our authors that places the current evidence in context, and highlights the role of marginalisation and stigma in reinforcing smoking. Key concepts from the personal recovery paradigm, such as connectedness, hope and empowerment are discussed. The relevance of these factors and the value of shared lived experience in challenging stigma, marginalisation and low expectations demonstrates the contribution that peer support can offer to support smoking cessation. Conclusions: Recovery-oriented approaches when integrated with existing evidence-based treatments designed to meet the needs of people living with schizophrenia have potential to improve outcomes by helping to take a more holistic approach to break down barriers and facilitate increased uptake of treatment and support. Further research to evaluate the effectiveness of integrated approaches is warranted.